Olive Tree (Olea europeae L.) Leaves: Importance and Advances in the Analysis of Phenolic Compounds - Leila Abaza; Amani Taamalli; Houda Nsir; Mokhtar Zarrouk (MDPI AG, 2015)
Phenolic compounds are becoming increasingly popular because of their potential role in contributing to human health. Experimental evidence obtained from human and animal studies demonstrate that phenolic compounds from Olea europaea leaves have biological activities which may be important in the reduction in risk and severity of certain chronic diseases. Therefore, an accurate profiling of phenolics is a crucial issue. In this article, we present a review work on current treatment and analytical methods used to extract, identify, and/or quantify phenolic compounds in olive leaves.